2014
DOI: 10.1021/es405186m
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Atmospheric Short- and Medium-Chain Chlorinated Paraffins in India and Pakistan using Polyurethane Foam Based Passive Air Sampler

Abstract: Production and use of chlorinated paraffins (CPs) have been increasing in India. Distribution of CPs in the area and vicinity have become a great concern due to their persistency and toxicity. Polyurethane foam based passive air samplers (PUF-PAS) was deployed in order to screen the presence of short-and medium-chain chlorinated paraffins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Polyurethane foams (PUF) and glass fibre filters (GFF) are typically Soxhlet-extracted with dichloromethane (DCM) (Li et al, 2012;Wang et al, 2013b;Chaemfa et al, 2014), 1:1 (v/v) ethyl acetate/methanol & toluene (Stevenson et al, 2011), or 9:1 (v/v) n-hexane/diethylether (DEE) (Stevenson et al, 2011). Ultrasonic bath extraction (USBE) has also been applied.…”
Section: Airmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethane foams (PUF) and glass fibre filters (GFF) are typically Soxhlet-extracted with dichloromethane (DCM) (Li et al, 2012;Wang et al, 2013b;Chaemfa et al, 2014), 1:1 (v/v) ethyl acetate/methanol & toluene (Stevenson et al, 2011), or 9:1 (v/v) n-hexane/diethylether (DEE) (Stevenson et al, 2011). Ultrasonic bath extraction (USBE) has also been applied.…”
Section: Airmentioning
confidence: 99%
“…Studies employing acid silica cleanup generally also reported relatively lower limit of detections (LODs) for SCCPs to those that did not, e.g. <0.2 ng m À3 compared to 2.65-10 ng m À3 (Fridén, 2010;Chaemfa et al, 2014). Reported LODs for MCCPs were 0.11 ng m À3 and 1.80 ng m À3 (Chaemfa et al, 2014).…”
Section: Airmentioning
confidence: 99%
“…The sampling was conducted using PASs equipped with polyurethane foam disks (14 cm diameter and 1.3 cm thick) that has been described elsewhere (Chaemfa et al, 2014). This technique can provide time-integrated sampling and has been applied in many studies on semi-volatile compounds in air (Jaward et al, 2005;Abdallah and Harrad, 2010).…”
Section: Sample Collectionmentioning
confidence: 99%
“…S2). Specifically, C 10 Cl 6-8 congeners were the prevailing ones in water samples (Lu, 2013;Yuan et al, 2012;Zeng et al, 2011bZeng et al, , 2012aZeng et al, , 2012b, while those with 5-7 chlorine atoms were dominant in air samples (Chaemfa et al, 2014;Fridén et al, 2011;Li et al, 2012;Wang et al, 2012Wang et al, , 2013bWang et al, , 2015. As for sediment and soil samples, the most abundant congeners possessed 5-10 chlorine atoms (Chen et al, 2011;Gao et al, 2012;Hüttig and Oehme, 2006;Iino et al, 2005;Iozza et al, 2008;Marvin et al, 2003;Štejnarová et al, 2005;Tomy et al, 1999;Wang et al, 2013bWang et al, , 2013cZeng et al, 2011aZeng et al, , 2012cZeng et al, , 2013, quite similar to those in food, human milk and wildlife samples (Harada et al, 2011;Thomas et al, 2006;Zeng et al, 2011b).…”
Section: Effect Of Chlorination Degree On Thermodynamic Properties Ofmentioning
confidence: 82%